The Rating of Perceived Exertion-Pediatric (RPE-P) Scale: Preliminary Validation - Brynn LiaBraaten; Stacy Stolzman; Pippa M. Simpson; Liyun Zhang; Taylor Brockman; Nina Linneman; Steven J. Weisman; Keri R. Hainsworth (MDPI AG, 2023)
Physical activity is critical to functional rehabilitation for youth with chronic pain, which may be especially true for those with co-occurring obesity. To facilitate the development of physical activity interventions for youth with chronic pain, the newly developed "Rating of Perceived Exertion-Pediatric" scale was modeled after the widely used pain numeric rating scale-11. This study is an initial evaluation of the scale in a sample of adolescents (n = 157, 13-17 years, 51% female) with four subgroups: (1) healthy controls (healthy weight/no pain); (2) chronic pain/healthy weight; (3) obese (no pain); (4) chronic pain/obese. Participants rated perceived exertion using the new scale and the Borg 6-20 Scale of Perceived Exertion while holding a three-minute yoga pose (Warrior II). In the whole sample, the Perceived Exertion-Pediatric scale showed good concurrent (p < 0.001), convergent (all ps < 0.05), discriminant (p = 0.431), and known-groups validity (all ps < 0.05). The chronic pain subgroup also showed good concurrent (p < 0.001), mixed convergent (ps < 0.001 to 0.315), and good discriminant validity (p = 0.607). Limitations include the restricted age range, lack of diversity, and lack of test-retest reliability. The RPE-P shows promise as an assessment tool for perceived exertion in adolescents with and without chronic pain.